2003
DOI: 10.1016/s1074-7613(02)00504-6
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan Captures, Protects, and Transmits HIV to T Lymphocytes

Abstract: This study demonstrates that syndecan functions as an in trans HIV receptor. We show that syndecan, when expressed in nonpermissive cells, becomes the major mediator for HIV adsorption. This adsorption is mediated by the binding of gp120 to the heparan sulfate chains of syndecan. Although syndecan does not substitute for HIV entry receptors, it enhances the in trans infectivity of a broad range of primate lentiviruses including primary viruses produced from PBMCs. Furthermore, syndecan preserves virus infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
212
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(224 citation statements)
references
References 27 publications
12
212
0
Order By: Relevance
“…We found that BMECs derived from all origins express high levels of heparan and chondroitin sulfates ( Fig. 1A and B), supporting the notion that proteoglycans are richly expressed on the surface of primary human endothelial cells derived from different tissues, including the brain (15,26,39,45,51). We found that BMECs derived from all origins express high levels of syndecan-2 and -4 ( Fig.…”
Section: Cell Surface Expression Of Proteoglycans On Primary Humansupporting
confidence: 72%
See 2 more Smart Citations
“…We found that BMECs derived from all origins express high levels of heparan and chondroitin sulfates ( Fig. 1A and B), supporting the notion that proteoglycans are richly expressed on the surface of primary human endothelial cells derived from different tissues, including the brain (15,26,39,45,51). We found that BMECs derived from all origins express high levels of syndecan-2 and -4 ( Fig.…”
Section: Cell Surface Expression Of Proteoglycans On Primary Humansupporting
confidence: 72%
“…We and others confirmed these findings by showing that HSPGs on the surface of specific cell types may greatly influence HIV infection (33,38,62,76,97). Primary human endothelial cells richly express HSPGs both in vitro and in vivo, and these HSPGs efficiently capture HIV-1 particles on the surfaces of the cells (15). Their abundance on the surface of primary endothelial cells and their high capacity to capture HIV-1 make HSPGs prime candidate receptors to facilitate the invasion of the brain by HIV-1.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, as filoviruses are pantropic and other infected cell types, such as endothelial and epithelial cells, do not express C-type lectins or TREMs, there might be other ubiquitous molecules, such as heparin-sulphate proteoglycan (HSPG; also known as SDC2) 13 and folate receptor-α (REF. 14), involved in viral-and host-receptor-mediated entry.…”
Section: Invariant Natural Killer T Cellmentioning
confidence: 99%
“…In our initial live-cell imaging studies using these VLPs, we had observed different types of particle behavior: free diffusion, brief touches with the plasma membrane, as well as a significant percentage of particles that displayed a rapid, presumably non-productive, immobilization at the plasma membrane in an apparently heparan sulfate dependent manner (Lampe et al 2007). Heparan sulfate has been reported to be involved in HIV-1 cell attachment and to be of functional importance in some types of host cells, but the overall role of heparan sulfate for HIV-1 infection is not entirely clear (Bobardt et al 2003;Moulard et al 2000;Parren et al 1998;Ugolini et al 1999;Zhang et al 2002). In the continuative study presented here, we had made use of the strengths of SVT to investigate the interactions of HIV-1 occurring at the plasma membrane in a quantitative manner.…”
Section: Introductionmentioning
confidence: 99%